Analysis of agglomeration particle size near the burning surface of aluminized solid propellant based on digital inline holography. (November 2021) - Sha, Benshang; Na, Xudong; Xia, Zhixun; Yan, Xiaoting; Li, Yang; Feng, Yunchao; Zi, Yabo
Abstract: Aluminum powder can increase the specific impulse and improve the combustion performance of a solid propellant; however, agglomeration can result in the loss of two-phase flow, a decrease in specific impulse of the propellant, and an increase in the thermal protection pressure of the motor structure. This study employs digital inline holography, which offers the advantage of non-contact three-dimensional measurements, to investigate the agglomeration particle size near the burning surface. This study aims to quantitatively analyze these particle size data to determine the effects of pressure, ammonium perchlorate particle size, coarse and fine ammonium perchlorate content ratio, and aluminum particle size on the agglomeration particle size distribution. The experimental results indicate that increasing the pressure from 0.1 MPa to 0.8 MPa reduces the average particle diameter of agglomeration by at least 9.6%, results in a more concentrated agglomeration particle size distribution, and decreases the volume and number proportion of agglomeration by approximately 7% and 17%, respectively. Furthermore, when the particle size of ammonium perchlorate decreases from 250 μm to 90 μm, the agglomeration particle size distribution becomes more concentrated, the average diameter of agglomeration decreases by at least 37.4%, and the number and volume proportion of agglomeration decrease by approximately 13% and 44%, respectively. The ratio of coarse and fine ammonium perchlorate content has a nonlinear effect on agglomeration. When this ratio is 0.6, the average agglomerate diameter decreases by at least 16%, the agglomeration particle size distribution is more concentrated than that the ratio is 0.39 and 1.29, and the agglomeration number and volume fraction decrease by more than 6% and 32%, respectively. Moreover, decreasing the initial aluminum particle size from 30 μm to 15 μm reduces the average agglomeration particle diameter by more than 21.6%, results in a more concentrated agglomeration particle size distribution, however, increases the number and volume proportion of agglomeration by approximately 17% and 8%, respectively. The conclusions of this study are expected to be significantly helpful in optimizing propellant formulation, reducing the particle size of aluminum agglomeration, and improving the combustion performance of propellants. Highlights: Influence of pressure, Al and AP on agglomeration particle size distribution was examined. The increase of pressure decreases the mean agglomerate diameter. The ratio of coarse and fine AP content has a nonlinear effect on agglomeration. Fine AP makes particle size distribution more concentrated. The decline of the initial Al size decreases the mean agglomerate diameter.